Efforts To Implement Integrated Assessment For Perpetrators Of Class I Narcotics Abuse For Themselves (Study At BNN Lampung Province) - Simeramisna, Brenda Sita (Fakultas Hukum Dehasen, 2025)
The state is responsible for eradicating narcotics crimes. Narcotics are substances or drugs derived from plants or non-plants, which can cause a decrease or change in consciousness, loss of pain and can cause dependence. In an effort to eradicate this crime, the National Narcotics Agency was formed because the distribution and abuse of narcotics has become rampant in society and government. Presidential Regulation of the Republic of Indonesia Number 23 of 2010 concerning the National Narcotics Agency Article 2. After discussions on the Joint Regulation, an Integrated Assessment Team Program was born, consisting of several teams. The teams in question include the Medical Team and the Legal Team which are tasked with carrying out an analysis of the role of suspects arrested at the request of investigators relating to illicit drug trafficking, especially for addicts.This research is focused on the efforts made by the Integrated Assessment Team (TAT) in handling the perpetrators of class 1 narcotics abuse for themselves. This research was conducted using a scientific method approach based on legal sources written in legislation (Law in Books) through 2 main sources at BNN Lampung. Each information is collected and an analysis is made by TAT BNN Lampung relating to the process of conducting assessments and procedures that must be in accordance with Law No. 35 of 2009 concerning narcotics which is then further regulated by PP No. 25 of 2011 concerning the Implementation of Mandatory Reporting of Narcotics Addicts. The process carried out by TAT is carried out with several stages such as information gathering by submitting files to the secretary and reviewed from a legal and medical perspective by each team. The implementation of this integrated assessment process does not require a long time, this is in accordance with the provisions regarding the work procedures of the integrated assessment team stipulated in article 14 paragraph (3) of the Regulation of the Head of the National Narcotics Agency Number 11 of 2014 concerning Procedures for Handling Suspects And / Or Defendants of Narcotics Addicts And Victims of Narcotics Abuse Into Rehabilitation Institutions. Based on some analysis, after taking care of all types of legal requirements in the assessment process, the legal apparatus determines prison as a form of punishment that is appropriate to provide a deterrent effect on the perpetrator. Thus, the application of the law that occurs at BNN Lampung related to TAT and the perpetrators of class 1 narcotics abuse is in accordance with applicable law. The above stages are a form of application of the Integrated Assessment Team (TAT) at the National Narcotics Agency (BNN) Lampung Province. After careful analysis, the Lampung Provincial BNN has implemented several stages and processes that must be carried out by TAT based on Law No. 35 of 2009 and in accordance with PP No. 25 of 2011. The results of this study prove that the Lampung Provincial BNN is in accordance with the application of TAT for class 1 drug abuse from oneself. The suggestion of this research is that the Integrated Assessment Team is expected to be able to overcome various factors that hinder the implementation of the integrated assessment process by increasing cooperation between law enforcement officials and government agencies in order to form good synergy in the implementation of integrated assessments. In addition, it can comply with all procedures in the law on the implementation of the use of class 1 narcotics to the maximum.